A Comparative Performance Analysis of ANN Algorithms for MPPT Energy Harvesting in Solar PV System - Roy R.B.; Rokonuzzaman M.; Amin N.; Mishu M.K.; Alahakoon S.; Rahman S.; Mithulananthan N.; Rahman K.S.; Shakeri M.; Pasupuleti J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Conjugate gradient method; Energy harvesting; Errors; Maximum power point trackers; Mean square error; Bayesian regularization algorithms; Comparative performance analysis; Energy harvesting systems; MATLAB/Simulink environment; Maximum Power Point Tracking; Scaled conjugate gradient algorithm; Scaled conjugate gradients; Solar photovoltaic system; Neural networks